Math, asked by Ashishmeena5634, 1 year ago

Verify that : 5/6×(-4/5+-7/10)=(5/6×-4/5)+(5/6×-7/10)

Answers

Answered by saivivek16
2

Step-by-step explanation:

Aloha !

5/6×(-4/5+(-7/10))

= -1.25

5/6×-4/5

=-0.66

5/6×-7/10

=-0.583

Thank you

Answered by Anonymous
3

Answer:

HEy maTe here's ur answer ___✌️❤️✌️

RHS-

  \frac{ - 2}{3}    - \frac{ 7}{12}  \\  - \frac{ - 15}{12}  \\  \frac{ - 5}{4}

LHS-

 \frac{5}{6} ( \frac{ - 8 - 7}{10} ) \\  \frac{ - 5}{4}

Plz... Follow mE ___☹️☹️☹️

Similar questions